- Analisis Kebangkrutan Melalui Perbandingan antara Model Altman Z-Score dan Springate pada Perusahaan Industri Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia: - - Fahrizal Fatkhur Rozi; Damayanti Damayanti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study is a bankruptcy analysis study that aims to prove and analyze the differences between the Atman Z-Score and Springate models in bankruptcy analysis in food and beverage industry companies listed on the Indonesia Stock Exchange.  This study uses secondary data in the form of company's annual financial report data sourced from the Indonesia Stock Exchange, namely www.idx.com.  There are 26 food and beverage industry companies listed on the Indonesia Stock Exchange in 2016-2020.  Sampling using purposive sampling technique.  There are 16 samples of companies that meet the criteria and have complete data in the last 5 years, thus getting as many as 80 observations.  The data analysis technique was testing the hypothesis using the Paired Sample t-Test and the Wilcoxon Signed Rank Test.  The results showed that there was a significant difference between the analysis of bankruptcy of the Altman Z-Score model and the Springate model of the food and beverage industry companies listed on the Indonesia Stock Exchange.  That the Altman Z-Score model is more stringent in assessing the bankruptcy rate than the Springate model.